Effect of vermicompost on pepper plants inoculated with Phytophthora capcisi. - Uribe-Lorío, Lidieth; Castro-Barquero, Leida; Arauz-Cavallini, Felipe; Henríquez-Henríquez, Carlos; Blanco-Meneses, Mónica (Agronomía Mesoamericana, 2014)
The objective of this paper was to evaluate under greenhouse conditions the effect of the application of vermicompost on incidence and severity of Phytophthora capcisi on pepper plants (Capsicum annuum). The experiment was conducted in February and March, 2012, at the Centro de Investigaciones Agronómicas, Sabanilla, San José, Costa Rica. A completely randomized design with 4 replicates and 8 plants per experimental unit, in a factorial design with doses (0, 25% and 50% v/v compost: soil), and inoculation (0 and 500 zoospores per gram of soil) was used. After 35 days, seedlings were transplanted, and two weeks later the plants were inoculated. The application of vermicompost caused a significant increase in fresh and dry shoot weight and dry root weigth, the higher the dose, the greater the increase. Plants of all treatments in which P. capsici was inoculated showed root symptoms; the treatment with 50% compost resulted in symptoms of wilt and the highest incidence and severity of the disease. The lack of differences in fresh and dry weight between inoculated and uninoculated treatments with doses of 25% of compost, suggest that the last could compensate for the damage caused by the disease. An observed lower concentration of nutrients in the plant tissues inoculated with the pathogen indicates that damage to the root may have affected nutrient uptake.